Tafsir Al-Qur’an dan Kekuasaan: Membaca Pandangan Bakri Syahid Tentang Nasionalisme Dalam Tafsir Al-Huda - Maulidiyah, Izatul Muhidah; Sultani, Hikmawati (UIN Sultan Syarif Kasim Riau, 2024)
This study aims to examine how Bakri Syahid’s Tafsir Al-Huda constructs notions of nationalism and legitimizes political authority through its interpretation of Q. al-Tawbah [9]:122 and its interrelation with Q. al-Nisāʾ [4]:59, situated within the socio-political context of Indonesia’s New Order and Javanese cultural milieu. Employing a qualitative, descriptive-analytical methodology, the research integrates content analysis with a sociology of exegesis. The primary object of analysis is the Tafsir Al-Huda text itself, while the formal object concerns the construction of religious nationalism. Primary data are obtained through close textual reading, complemented by secondary sources encompassing studies on Indonesian exegesis, the intersection of religion and politics, and relevant cultural materials. The analytical process involves data reduction, thematic categorization, and historical-contextual interpretation. The findings reveal three principal insights. First, the interpretation of jihad in Q. 9:122 is reoriented toward an ethos of civic engagement and development, metaphorically likened to state “departments,” thereby positioning the exegesis as a form of policy discourse. Second, the concept of “ulū al-amr” in Q. 4:59 is construed as faithful leadership that ensures welfare defined as a just and prosperous social order and commands obedience insofar as it serves the public interest, drawing upon modern exegetical sources and Javanese ethical traditions for legitimation. Third, the diverse range of sources including tafsir, fiqh, social sciences, and cultural texts constitutes an intertextual framework that reinforces the alignment of religion and state under the New Order regime. This study concludes that Tafsir Al-Huda functions as an ideological exegesis that interweaves religion, culture, and statecraft, illustrating how exegesis serves as a medium for shaping religious nationalism. Abstrak: Penelitian ini bertujuan untuk menganalisis bagaimana Tafsir Al-Huda karya Bakri Syahid membingkai nasionalisme dan legitimasi kekuasaan melalui penafsiran Q.S. At-Taubah [9]:122 serta keterkaitannya dengan Q.S. An-Nisa’ [4]:59, dalam konteks Orde Baru dan budaya Jawa. Metode yang digunakan bersifat kualitatif deskriptif-analitis dengan analisis isi dan sosiologi tafsir; objek materialnya ialah kitab Tafsir Al-Huda, sedangkan objek formalnya konstruksi nasionalisme religius. Data primer berasal dari telaah naskah, dan data sekunder meliputi kajian tafsir Indonesia, politik agama, serta sumber budaya; analisis dilakukan melalui reduksi, kategorisasi tema, dan interpretasi historis-kontekstual. Hasil penelitian menunjukkan tiga temuan utama. Pertama, penafsiran jihad pada Q.S. At-Taubah [9]:122 digeser menjadi etos partisipasi kewargaan dan pembangunan, dengan analogi departemen-departemen negara, sehingga tafsir berfungsi sebagai wacana kebijakan. Kedua, konsep ulū al-amr pada Q.S. An-Nisa’ [4]:59 diartikulasikan sebagai kepemimpinan beriman yang menyejahterakan (adil-makmur) dan menuntut kepatuhan selama berbasis kemaslahatan, seraya menyerap rujukan tafsir modern dan warisan Jawa sebagai legitimasi etis. Ketiga, ragam sumber rujukan tafsir, fikih, ilmu sosial, dan naskah budaya membentuk bangunan interteks yang meneguhkan sinkronisasi agama-negara pada masa Orde Baru. Penelitian ini menegaskan bahwa Tafsir Al-Huda bekerja sebagai tafsir ideologis yang merajut agama, budaya, dan negara, sekaligus memperlihatkan bagaimana tafsir menjadi medium pembentukan nasionalisme religius.